Working Model for Strategic Communication Persuading the Hostile Target during Interrogation - Yadav, Ravinder (Defence Life Science Journal, 2021)
The model aims to assist the security force personnel in the new era of warfare where the enemy is eliminated not by the weapons but by the information wars first. Also, a robust shield is required to counter it in the form of information-operations. The locals are made resilient enough to counter the information-war of the enemies. The interactions with the locals are required to convert into opportunities to win their hearts and minds. Generally, in a hostile environment, any interaction with the people turns in the form of an interrogation, since the trust is low and the stakes are high. The present paper accumulated the experiential knowledge from the experts operated in the vulnerable and hostile areas, to develop a scientific model of strategic-communication. The model explains the psychological techniques step by step, used by the experts to convert interrogation as an opportunity to build a sustainable relationship of support and cooperation.